2012
DOI: 10.1021/jo202505h
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Synthesis of Branched DNA Hybrids Based on Dimer Phosphoramidites and Phenolic or Nucleosidic Cores

Abstract: Branched oligonucleotides with "CG zippers" as DNA arms assemble into materials from micromolar solutions. Their synthesis has been complicated by low yields in solid-phase syntheses. Here we present a solution-phase synthesis based on phosphoramidites of dimers and phenolic cores that produces six-arm or four-arm hybrids in up to 61% yield. On the level of hybrids, only the final product has to be purified by precipitation or chromatography. A total of five different hybrids were prepared via the solution-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…To avoid the costly methyl-protected monomers used earlier, [43] we limited ourselves to the more common cyanoethyl phosphoramidites and used linear syntheses (Scheme 1b). Further, we suspected that the reactivity of monomers would be higher than that of dimers.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the costly methyl-protected monomers used earlier, [43] we limited ourselves to the more common cyanoethyl phosphoramidites and used linear syntheses (Scheme 1b). Further, we suspected that the reactivity of monomers would be higher than that of dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Crystals of porous organic cages that absorb gases are also known, and porous liquids are beginning to emerge, but what would constitute a good crystalline matrix for formulating liquid reagents is unclear. While studying organic cores for matrix‐forming DNA hybrids, we observed that 1,3,5,7‐tetrakis(2,4‐dimethoxyphenyl)adamantane (TDA) readily includes small organic molecules in the unit cell of its crystal structures . Even though a solvent‐free crystalline form is known, TDA crystallizes with many different guest molecules.…”
Section: Figurementioning
confidence: 99%
“…Because of multivalent interactions, dinucleotide arms of the sequence 5′‐CG‐3′ suffice to induce the formation of materials upon hybridization of hybrids with four, six or eight arms in aqueous buffer containing magnesium ions 24, 25. Efficient and scalable solution‐phase syntheses make these compounds available at a fraction of the cost of linear oligonucleotides 26, 27. Uptake of DNA staining agents demonstrated that the three‐dimensional networks can accommodate guest molecules in the solids formed upon hybridization,24, 27 but it was unclear whether drugs would be incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Efficient and scalables olution-phase syntheses make these compounds available at af raction of the cost of linear oligonucleotides. [26,27] Uptake of DNA staininga gentsd emonstrated that the three-dimensional networks can accommodate guest molecules in the solids formed upon hybridization, [24,27] but it was unclear whether drugs would be incorporated. This promptedu st ot est whether hybrids with CG zippera rms can act as matrix for the formulation of APIs.…”
Section: Introductionmentioning
confidence: 99%